POLYPHENOLIC CONTENT AND IN VITRO ANTIOXIDANT EVALUATION OF THE STEM BARK EXTRACT OF PELTOPHORUM AFRICANUM SOND (FABACEAE) - Okeleye, B I; Nongogo, Vuyokazi; Mkwetshana, Noxolo T; Ndip, Roland N (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Peltophorum africanum has been traditionally used to relief stress induced diseases. The study was aimed to evaluate the antioxidant activities of ethyl acetate extract. Material and methods: The in vitro antioxidant activities of Peltophorum africanum stem bark extract was examined in this study by means of +radical scavenging and ferric reducing power analysis using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2`-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid (ABTS) kit, hydrogen peroxide (H2O2), iron (iii) chloride (Fe3+) and nitric oxide (NO). In assessing the likely effects of secondary metabolites on the activities observed; total proanthocyanidins, phenolics, flavonols, and flavonoids were determined using standard phytochemical methods. Data was analyzed by ANOVA test and the p-value < 0.05 was considered significant. Results: Extract scavenging activity of 88.73± 6.69 % (25 µg mL-1), 53.93±1.09 % (25 µg mL-1), 87.293±6.64 % (25 µg mL-1), 10.55±2.16 mM (0.42 mM) and 3.8115±0.06 (25 µg mL-1) were recorded for H2O2, NO, DPPH, ABTS and Fe3+ reducing power respectively. These values were comparable to the standard compounds; DBPC*BHT, L (+) - Ascorbic acid and Trolox™ (p < 0.05). Proanthocyanidins (92.18±4.68 mg/g) occurred more (p < 0.05) in the extract when compared to all other compounds tested: phenolics (60.53±1.46 mg/g) > flavonoids (18.37± 2.11 mg/g), > flavonols (11.20±3.90 mg/g). However the difference between flavonols and flavonoids was not significant (p > 0.05) at 95% confidence interval.Conclusion: The results of this study validated the folkloric use of P. africanum which could be exploited as an easily available and a cheaper source of natural antioxidants.